Multivariable Logistic Regression of Modifiable Stunting Risk Factors in Kubu Raya - Linda Suwarni; Selviana Selviana (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Stunting in toddlers remains a public health challenge in Indonesia, especially in areas with high prevalence such as Kubu Raya District, which reaches 25.4%. Although multiple risk factors for stunting have been identified in the broader literature, evidence from district-level settings in West Kalimantan remains limited, and the relative contribution of modifiable determinants within this specific context has not been systematically examined. This study aims to analyze the determinants of stunting in children aged 24–59 months in Kubu Raya District, West Kalimantan. Methods: A cross-sectional study was conducted on 435 children aged 24–59 months selected through multistage random sampling. Data were collected using a structured questionnaire and anthropometric measurements. The variables studied included the age of introduction of complementary foods (MP-ASI), exclusive breastfeeding, maternal health education (KIE), gestational age, low birth weight (LBW), and birth spacing. Nutritional status was determined based on height-for-age (HAZ) using the 2006 WHO standards. Data analysis used chi-square tests and multiple logistic regression. Results: The prevalence of stunting reached 40.7% (177 out of 435 infants). In the bivariate analysis, all variables showed a significant association with stunting: inappropriate age for introducing complementary foods (OR=6.527; 95% CI: 2.177-19.567; p=0.000), not receiving exclusive breastfeeding (OR=2.372; 95% CI: 1.827–3.080; p=0.000), lack of exposure to health education (OR=1.285; 95% CI: 1.026–1.610; p=0.032), high-risk pregnancy (OR=1.478; 95% CI: 1.184–1.845; p=0.001), low birth weight (OR=1.483; 95% CI: 1.101–1.997; p=0.024), and risky birth spacing (OR=1.280; 95% CI: 1.022–1.602; p=0.033). Multivariable logistic regression retained absence of exclusive breastfeeding as the sole independent predictor of stunting (AOR = 3.289; 95% CI: 2.096–5.164; p < 0.000; reference: exclusively breastfed). Conclusion: Exclusive breastfeeding is the primary determinant of stunting prevention after controlling for other risk factors. Stunting prevention programs should prioritize increasing exclusive breastfeeding coverage through comprehensive education, sustained lactation support, and policies that promote optimal breastfeeding practices. Integration of nutritional interventions within the 1000 Days of Life framework is necessary to achieve national stunting reduction targets.